The Greater Father Involvement in Parenting, The Better Self-Esteem Develops - Syahputri, Wenny Hikmah; Azahra, Adisa; Risnawati, Erna (Universitas Mercu Buana Jakarta, 2025)
This research investigates the impact of father involvement on the self-esteem of individuals in early adulthood. Employing a quantitative approach, the study utilized a father involvement scale adapted from Risnawati et al. grounded in the theoretical framework of Gancy and Van Dulman, alongside a modified version of Rosenberg’s Self-Esteem Scale as adapted by Maroqi. The sample consisted of 188 male and female participants aged 18 to 25 who currently reside with their fathers. Participants were selected through an accidental sampling technique. Data analysis using simple linear regression revealed a statistically significant relationship between father involvement and self-esteem. These findings indicate a positive and meaningful contribution of father involvement to the development of self-esteem during early adulthood.